1990
DOI: 10.1093/brain/113.5.1361
|View full text |Cite
|
Sign up to set email alerts
|

Familial Paroxysmal Kinesigenic Ataxia and Continuous Myokymia

Abstract: A large family with paroxysmal ataxia and continuous myokymic discharges is described. The disorder is of autosomal dominant inheritance. During attacks coordination of movements and balance are disturbed; often a postural tremor of the head and the hands and fine twitching in some of the facial and hand muscles are present. The attacks usually last a few minutes and may occur several times per day. They first appear in childhood and tend to abate after early adulthood. The attacks are frequently precipitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 0 publications
4
90
1
1
Order By: Relevance
“…Lubbers et al 40 studied the response of an EA-1 family to acetazolamide. All six members were affected by paresthesia (in accordance with reports from other families 10 ), and this caused the medication to be ACZ ϭ acetazolamide; EA-1 ϭ episodic ataxia type 1; N/A ϭ data not available.…”
Section: Treatmentsupporting
confidence: 67%
See 1 more Smart Citation
“…Lubbers et al 40 studied the response of an EA-1 family to acetazolamide. All six members were affected by paresthesia (in accordance with reports from other families 10 ), and this caused the medication to be ACZ ϭ acetazolamide; EA-1 ϭ episodic ataxia type 1; N/A ϭ data not available.…”
Section: Treatmentsupporting
confidence: 67%
“…To date, 11 individuals from four unrelated families have been reported to have epilepsy. 10,17,27,37 Van Dyke et al 27 described a female with generalized motor seizures and an abnormal EEG who had a partial response to phenytoin. Brunt and van Weerdan 10 in 1990 identified three members of an EA-1 family with 28 affected members who had abnormal EEGs.…”
Section: Epilepsy and Ea-1mentioning
confidence: 99%
“…It caused fewer side effects and was most effective in dosages between 50 and 300 mg daily. 62 Nevertheless, ACTZ is the drug of first choice, with sulthiame as an alternative treatment option. Recently, Scoggan et al 63 identified a new missense mutation in exon 12 of the CACNA1A gene from a patient with EA 2; the symptoms were controlled with a combination of ACTZ and valproic acid.…”
Section: Acetazolamidementioning
confidence: 99%
“…The disease is characterized by symptomatic attacks of imbalance and uncontrolled movements that may be triggered by physical or emotional stress (3,8,12,22,60). The duration of the attacks of ataxia varies: they may occur several times a day or once a year.…”
Section: -Episodic Ataxia Type 1 (Ea1) Is Amentioning
confidence: 99%
“…Although the symptoms vary between and within families, two symptoms are always observed: an ataxic gait during attacks and myokymia. The latter symptom is characterized by continuous muscle activity that can be detected as a rhythmic electromyography activity with a pattern of repeated duplets and multiplets (12,22). Genetic linkage studies have localized the EA1 locus to chromosome 12p13 (36).…”
Section: -Episodic Ataxia Type 1 (Ea1) Is Amentioning
confidence: 99%